EU anti-discrimination law: Has the CJEU stopped moving forward?. Issue 2 (June 2018) - Howard, Erica
This article analyses the protection which two European Union (EU) Directives, adopted in 2000, provide against discrimination on the grounds of racial and ethnic origin, religion or belief, disability, age and sexual orientation. This protection is not the same for all these grounds, and this has led to what is often referred to in the literature as a hierarchy of discrimination grounds. The article examines these differences in protection against discrimination and the reasons for them and includes an analysis of the influence of the case law of the Court of Justice of the European Union (CJEU) on the development of this area of law. The argument in this article is that the CJEU has generally given a purposive and expansive interpretation to the provisions and has expanded the protection against discrimination in many cases, but three recent cases seem to form an exception to this. Possible reasons for this recent reticence are given.